واقع وتحديات تكتل بريكس في مجابهة الحمائية الجديدة والهيمنة الأمريكية على الاقتصاد العالمي - كحلات عنتر; بالغيثار مسعود (جامعة الوادي University of Eloued, 2024)
تهدف الدراسة إلى تسليط الضوء على الدور الذي تلعبه دول البريكس في مجابهة تصاعد الحمائية الجديدة التي تبنتها الدول المتقدمة وعلى رأسها الولايات المتحدة الأمريكية، والتي سعت مع حلول سنة 2018 إلى تبني سياسات حمائية معلنة لحماية مصالحها الاقتصادية. وقد خلصت الدراسة إلى أن تكتل البريكس يسعى قدما للقيام بإصلاحات عميقة في النظام العالمي الحالي نتيجة السيطرة الأحادية للولايات المتحدة الأمريكية، وأكدت دول البريكس على ضرورة تكثيف الجهود والتنسيق لقيام نظام عالمي متعدد الأطراف، وتكوين مؤسساته المالية، وقائم على مبادئ منظمة التجارة العالمية، تكون فيه حرية المعاملات التجارية والاستثمار ومحاربة كل أشكال الحمائية الجديدة والممارسات التجارية الغير عادلة والتي من شأنها عرقلة حركة تدفقات التجارة ورؤوس الأموال.The study aims to shed light on the role played by the BRICS countries in confronting the rise of new protectionism adopted by developed countries, led by the United Stated of America, which sought at the beginning of 2018 to adopt declared protectionist policies to protect its economic interests. The study concluded that the BRIC bloc seeks to carry out profound reforms in the current global system, as a result of the unilateral control of the United States of America. The BRICS countries stressed the need to intensify efforts and coordination to establish a global multilateral system and the formation of its financial institutions, based on the principles of the World Trade Organization, in which there is freedom of commercial transactions and investment, and to fight all forms of new protectionism and unfair trade practices that would obstruct the movement of trade and capital flows.
The reality and challenges of the BRICS bloc in facing the new protectionism and US hegemony over the global economy
Keywords: تكتل بريكس; حمائية جديدة; نمو الاقتصاد العالمي; حرب تجارية; حرية التجارة; BRICS bloc; new protectionism; global economic growth; trade war; free trade